Prevalence and predictors of right ventricular dysfunction in cancer patients treated with cardiotoxic chemotherapy – a prospective cardiovascular magnetic resonance study. (14th October 2021) - Labib, D; Dykstra, S; Satriano, A; Mikami, Y; Prosia, E; Flewitt, J; Howarth, A G; Lydell, C P; Kolman, L; Paterson, D I; Oudit, G Y; Pituskin, E; et al.
Abstract: Background: Right ventricular (RV) function has an established incremental prognostic value in cardiomyopathy. Studies on cancer therapeutics-related cardiac dysfunction (CTRCD) primarily focused on the left ventricle (LV), with conflicting results from small studies dedicated to RV dysfunction. Purpose: We sought to investigate the influence of chemotherapy on RV function relative to LV function using serial cardiac magnetic resonance (CMR). Methods: Patients were enrolled as part of Cardiotoxicity Prevention Research Initiative (CAPRI) Registry aimed at evaluating CMR-based markers for surveillance of CTRCD. Patients underwent non-contrast CMR imaging prior to initiation of anthracyclines and/or trastuzumab and serially every 3 months during the first year, then annually thereafter. We included patients who had a baseline and ≥1 follow-up scan and excluded those with baseline LV ejection fraction (EF)<50%, providing 320 patients completing 1, 453 CMR studies. Cine images were analysed to calculate chamber volumes indexed to body surface area and EF. We defined LV CTRCD using CMR modality specific criteria of a drop in LV EF ≥5% from baseline to <57%; RV CTRCD as a drop ≥5% to <49% in females and <47% in males. We used linear mixed models to study the changes in ventricular volumes and EF with time. Results: The majority of patients were females (80%), had breast cancer (68%) or lymphoma (32%), with a mean age of 52.7±13 years. Figure 1 shows temporal changes in mean ventricular volumes and function over the first year. Mean changes in RV function followed those of the LV, with the nadir of EF and maximum of volumes occurring at 6 months. Respective values for mean decrease in LV and RV EF at this time point versus baseline were 4.1 and 2.9% (p<0.001). Concomitant mean increase in indexed RV end-diastolic (ED) and end-systolic (ES) volumes were 1.6 and 2.7 ml/m 2 (p=0.2 and <0.001). There was significant interaction of chemotherapy regimen with time for RV volumes (p=0.001 and 0.003), but not RV EF (p=0.7), with worst changes occurring with combined anthracyclines and trastuzumab. In all, 70 (22%) and 28 (9%) patients met criteria for LV and RV CTRCD, respectively. Among those who developed RV CTRCD, 10 had persistently normal LV function. Figure 2 shows the results of logistic regression to predict RV CTRCD. Significant univariable predictors included combined chemotherapy regimen and baseline LV and RV volumes and LV EF. Adjusting for age, sex, and chemotherapy regimen, baseline RV ED volume remained associated with RV CTRCD (odds ratio 1.6; p=0.005). Conclusion: In this large study, RV volumes and function were similarly influenced by chemotherapy versus comparable LV-based measures. Using similar threshold criteria, the incidence of RV CTRCD was lower than for LV CTRCD; however, one third of those who develop RV CTRCD showed normal LV function. Future studies are warranted to study the prognostic influence of RV injury in cancer patients. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Alberta InnovatesGenome Alberta